Diagnóstico de la salud y la Inclusión Social del adulto mayor en el cantón Ibarra: Diagnosis of health and social inclusion of the elderly adult in Ibarra (La U Investiga, 2017)
Considered older beginning at age 65, has a relevant constitutional where the Constitution of the Ecuadorian State assumes this responsibility basing rights in the elder’s law (2006), the present research work aims to make a diagnosis on the inclusion of this age group focused on the Group of adults over 70 yearsold , where it refuses the recognition of their family and community inclusion so, stewardship is, between the State, the family and the community, this study takes place in urban and rural parishes in the canton Ibarra, the diagnosis was based on a quantitative methodology; the type of research was descriptive and field, whose results and discussion rests with a collection and review documented bibliography, the techniques used were the survey and observation, and instruments the questionnaire and the form field. From these data we can affirm the existence of a large population of older adults in the city, which due to their physical, mental, and emotional conditions find it difficult, sometimes impossible to live under normal conditions from the rest of society, factors that preclude their social and family integration, these parameters show a lack of awareness of community and family as for priority attention and to ignorance of the law.
Keywords: Elderly; Insertion; Canton Ibarra